Aquaponics as a sustainable alternative to new land reclamation and conventional agriculture in Egypt - El Essawy, Hisham Ahmed Samy (AUC Knowledge Fountain, 2017)
Agriculture in Egypt is facing dramatic changes that affect its productivity, and accordingly the Egyptian economy. Egypt started in the 1930s, expanding agricultural land through land reclamation projects. Many of these projects did not perform as expected or planned due to lack of water and other challenges. While land reclamation and conventional agriculture techniques have a lot of technical, social, and economical problems in Egypt; soilless agriculture and aquaponics are being successfully used in other regions for urban food production as a sustainable solution. Aquaponics is a technique that integrates fish and crop productions by bringing aquaculture with hydroponics (soilless planting) together into one system. Although aquaponics has shown promising results in different regions worldwide, there are questions that need answering about the most suitable type of aquaponics for food production in Egypt. Aquaponics have been investigated in this work in order to identify its potentials, hence recommend the suitable aquaponics systems for Egypt. The thesis shows that aquaponics is an ally or alternative to conventional agriculture and land reclamation in Egypt. In this thesis, two different Aquaponics systems were tested in an experiment, in the American University in Cairo, to determine which system design will be more efficient and productive for use in Egypt on a larger scale. The production and crops variety were more promising in the Integrated Aqua Aegaculture System than the Deep Water Culture aquaponics system. The elemental analysis results of water and plants samples, from both aquaponics systems, show that the Integrated Aqua Vegaculture system has more potential than the Deep Water Culture system, especially in Egypt under certain boundary conditions.